Plant ABC transporters: time for biochemistry?. (9th October 2015) - Lefèvre, François; Baijot, Amandine; Boutry, Marc
Abstract : ATP-binding cassette (ABC) proteins form a large and ubiquitous family, most members of which are membrane-associated primary transporters. Plant genomes code for a particularly large number of these ABC proteins, with more than 120 genes present in both Arabidopsis thaliana and Oryza sativa (rice). Although plant ABC transporters were initially identified as detoxifiers, sequestering xenobitotics into the vacuole, they were later found to be involved in a wide range of essential physiological processes. Currently, the exact substrates transported by most of these transporters are still unknown and we therefore cannot exclude that a single substrate (e.g. a hormone) is responsible for the diversity of physiological roles. This gap in our knowledge is mainly due to the fact that only a few studies have used direct methods to identify the substrates of these membrane transporters. To address this issue, transport assays involving isolated cells, vesicular membranes or reconstituted liposomes are essential. In this review, we will highlight the importance of the direct biochemical characterization of plant ABC transporters and give some insights into the current status of the homologous and heterologous expression of such proteins.